An Eoraip: Gaelic Ireland in Medieval and Early Modern Europe - Kane, Brendan,; Wadden, Patrick, (Late Antiquity and Medieval Studies E-Books Online, Collection 2025., 2025)
Medieval and early modern Irish scholars thought of themselves as Europeans. As an expression of territorial association, this belief reflects both their familiarity with the geographical traditions of Antiquity and the integration of their society into economic, cultural, and political networks that spanned the continent. But it was also an articulation of a perceived cultural affinity often denied in modern scholarship. The chapters in this volume examine the many and various ways that Gaelic Ireland was integrated into the broader, European world, focusing on literature and learning; real-world politics, economics, and travel; and questions of identity. Contributors are: Rachel Brody, Michael Clarke, Simon Egan, Deborah Hayden, Brendan Kane, Victoria L. McAlister, Ken Ó Donnchu, Patricia Palmer, Brian Stone, and Patrick Wadden.